2017
DOI: 10.18632/oncotarget.20325
|View full text |Cite
|
Sign up to set email alerts
|

Association between essential hypertension and bone mineral density: a systematic review and meta-analysis

Abstract: BackgroundWe conducted this systematic review and meta-analysis to evaluate the association between essential hypertension (EH) and bone mineral density (BMD).Results17 articles were included in our meta-analysis, with a total of 39,491 patients. Of these, 13,375 were patients with EH and 26,116 were patients without EH. Meta-analysis results showed that EH can reduce the BMD of the lumbar spine (95% CI: −0.08∼0.01, P=0.006), femoral neck (95% CI: −0.09∼-0.02, p = 0.001), ward's triangle (95% CI: −0.45∼-0.25, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 28 publications
2
34
0
1
Order By: Relevance
“…Diastolic blood pressure was not associated with BMD or osteoporosis. This observation contradicts the findings of a meta-analysis, which showed that blood pressure is negatively associated with BMD and positively with increased risk of osteoporosis [40]. It is generally agreed that high blood pressure increases the excretion of calcium, thus elevating parathyroid hormone level and bone resorption [9].…”
Section: Discussionmentioning
confidence: 83%
“…Diastolic blood pressure was not associated with BMD or osteoporosis. This observation contradicts the findings of a meta-analysis, which showed that blood pressure is negatively associated with BMD and positively with increased risk of osteoporosis [40]. It is generally agreed that high blood pressure increases the excretion of calcium, thus elevating parathyroid hormone level and bone resorption [9].…”
Section: Discussionmentioning
confidence: 83%
“…(24) Recently, DPP3 was reported to effectively digest the Angiotensin-II peptide and to exert a critical function in blood pressure control during hypertension, (25,26) possibly through Nrf2 regulation. (27) The association between hypertension and BMD is indeed debated (67) ; therefore, based on literature and on our results it would be interesting to further investigate this aspect taking advantage of our newly generated Dpp3 KO mouse.…”
Section: Discussionmentioning
confidence: 90%
“…Since osteoporotic fractures impose a huge social and economic burden, enormous effort has been undertaken to manage this problem, particularly the development of viable preventive and therapeutic approaches for osteoporosis. Advanced age [121], sex hormone deficiency [122], the use of medication [123], alcohol consumption [124], smoking [125], as well as underlying medical complications such as hypertension [126], diabetes [127], hyperlipidemia [128] and MetS [129][130][131] are the common contributing factors for poor bone health.…”
Section: Effects Of Tocotrienol On Osteoporosismentioning
confidence: 99%